A novel strategy with combined assays for detection of anti-neutrophil cytoplasmic antibody (ANCA) in clinically ANCA-negative granulomatosis with polyangiitis patients. Issue 6 (December 2017) - Tateyama, Kaori; Kodama, Satoru; Kishibe, Kan; Harabuchi, Yasuaki; Suzuki, Masashi
Abstract: Objective: Granulomatosis with polyangiitis (GPA) that is localized to the upper airway presents a diagnostic challenge because of a tendency towards anti-neutrophil cytoplasmic antibody (ANCA)-negativity. The purpose of this study was to investigate whether positivity of ANCA detection might be elicited with combined use of enzyme-linked immunosorbent assay (ELISA) kits. Methods: Twenty-nine serum samples obtained from GPA patients were used in this study. In addition to routine biochemical investigation for ANCA, tests for detecting PR3-, MPO-ANCAs, and minor ANCAs were performed with commercially available ELISA kits. Cytoplasmic (C)-ANCA and perinuclear (P)-ANCA were evaluated using the indirect immunofluorescence (IIF) technique. Results: Twelve patients were positive for PR3- or MPO-ANCA in the clinical laboratory test, and 17 patients were negative for both ANCAs. Of the 17 ANCA-negative patients, four were positive for PR3- or MPO-ANCA, and three were positive for minor ANCA according to results obtained from six different ELISA kits. These findings indicated that performing detection tests with six different ELISA kits might improve the positivity of ANCA and might contribute to establishing the diagnosis of ANCA-associated vasculitis. Together with results from IIF, the samples of eight patients with clinically ANCA-negative results (8/17, 47.1%) were converted to ANCA-positive results, and the ANCA detection rate was significantly improved from 12/29 (41.4%) to 20/29 (69.0%, p = 0.03). Conclusions: Additional detection techniques should be used to confirm the results of clinically ANCA-negative samples, particularly when vasculitis is suspected. Minor ANCAs should also be evaluated with detection tests when PR3- and MPO-ANCA are negative.